الأفعال المتضمنة في القول (نماذج مختارة من جامع العلوم والحكم لابن رجب) –مقاربة تداولية - تواتي طليبة، شفيقة, بكاكرة، منى (جامعة الوادي University of Eloued, 2019)
الملخص: تناولت هذه الدراسة الأفعال المتضمنة في القول (نماذج مختارة في جامع العلوم والحكم لابن رجب) –مقاربة تداولية- وتهدف إلى الوقوف على دور متضمنات القول في العملية التواصلية من خلال تأويل المخاطَب، بهدف الكشف عن المضامين الظاهرة والمضمرة في الخطاب، حيث بُدأت بقدمة يليها مدخل وقد عنون بمفاهيم نظرية جاء فيه كل ما يتعلق بالتداولية. الفصل الأول: خصص للافتراض المسبق، مفاهيم نظرية وملامحه في الحديث النبوي الشريف. الفصل الثاني: القول المضمر، مفاهيم نظرية وملامحه في الحديث النبوي الشريف. خاتمة توصلنا فيها إلى أهم النتائج. This study dealt with the acts included in the saying (selected models in the mosque of science and governance of Ibn Rajab) - a deliberative approach - It aims to identify the role of the implications of the communication in the communication process through the interpretation of the address, in order to reveal the contents manifest and implied in the discourse, where it began with an introduction followed by an introduction and have meanings of theoretical theory in which all related to deliberation. Chapter I: Pre-assumptions, concepts and features of the Prophet's Hadith. Chapter II: the implicit view, the concepts of the theory and its features in the Hadith of the Prophet. Conclusion We reached the most important results.
Keywords: التداولية، متضمنات القول، الافتراض المسبق، القول المضمر، الحديث النبوي الشريف; deliberative, implication, preconceived, implicit, prophetic Hadith